Development and implementation of an aspiration pneumonia cause investigation algorithm. (14th November 2022) - Yoshimatsu, Yuki; Tobino, Kazunori; Ortega, Omar; Oda, Hiroyuki; Ota, Hiroaki; Kawabata, Takafumi; Hiramatsu, Yuri; Murakami, Yosuke; Clavé, Pere
Abstract: The diagnostic criteria of aspiration pneumonia have not been established, and it remains an underdiagnosed entity. Diagnosis and cause investigation is essential in improving the management of aspiration pneumonia. The Japanese Respiratory Society Guidelines for the Management of Pneumonia in Adults (JRS Guidelines) show a list of risk factors for aspiration pneumonia. We developed an algorithm to aid physicians in evaluating these possible underlying factors and guide their management with a focus on aspiration pneumonia. The algorithm was developed based on the JRS Guidelines. The algorithm suggested dysphagia screening, pneumococcal and influenza vaccination, and other preventative measures for pneumonia. The algorithm was implemented in the acute setting of a general hospital among older patients admitted with pneumonia. Their outcomes were compared with a historical control group constituting similar patients from the previous year. Forty patients with pneumonia were assessed with the algorithm group, and 44 patients were included in the control group. In the algorithm group, significantly more cases (95.0% vs. 15.9%, p  < 0.01) underwent early screening for a swallowing disorder. Two patients in the algorithm group were diagnosed with a new condition causing aspiration pneumonia, as opposed to none in the control group. Drugs with a potential risk for aspiration were identified and discontinued in 27.5% of the patients in the algorithm group and 4.5% in the control group. In conclusion, an aspiration pneumonia cause investigation algorithm translating the JRS guideline approach into practice enhanced the rate of swallow screening and preventative measures for aspiration. Abstract : Aspiration pneumonia remains an underdiagnosed and unestablished diagnosis. We propose the use of an algorithm (developed based on the JRS guidelines) to enable adequate management of older adults with pneumonia. When implemented in an acute setting, the algorithm enhanced the diagnosis of causative conditions, swallow screening, and preventative measures.